Penggunaan Strict Liability Dalam Pertanggungjawaban Secara Perdata Pada Sengketa KLHK Melawan PT. Waringin Agro Jaya - Kurniawan, Denis (UIN Syarif Hidayatullah Jakarta, 2024)
The right to access a good and healthy environment is a right for all citizens guaranteed by the 1945 Constitution. The right to obtain a good and healthy environment is not only limited by the rights of the current generation but also a right that future generations can feel with pro-environment sustainable development. The state's right to sue the central government through the Ministry of Environment and Forestry is an effort to protect the environment from polluters and/or environmental destroyers, one of which is filing a civil lawsuit. This research is a normative or doctrinal legal research with a statute, conceptual, and case approach. This study concludes that the legal liability carried out by PT Waringin Agro Jaya can be justified based on strict liability because, in principle, strict liability is a liability without fault in every business or activity categorized as Abnormally Dangerous Activity.